Inverse Margin Filtration Applied for Surface Water Treatment - Bello, Sergio Luiz; Nonato, Thyara Campos Martin; Filho, Paulo Belli; Neto, Augusto Oliveira; Sens, Maurício Luiz (Anuário do Instituto de Geociências, 2021)
Technologies to be applied under the context of protection and revitalization of surface water must be developed and improved in order to enhance the quality of aquatic ecosystems. In this way, this study aimed to evaluate the treatment performance of an inverse margin filtration system (IMF) applied in surface water treatment. The IMF was monitored during 1 year through the classic water quality parameters, and thus the treatment performance along the filtration path was identified. The results showed an average removal efficiency of 41% for turbidity, 35% for apparent color, 43% for true color, 26% for total suspended solids and total organic carbon, 53% for nitrogen, 46% for phosphorus, 91% for iron, 8% for manganese, and 100% for fecal coliforms. In this way, the IMF system proved to be a technology that can be applied in the treatment of water in lentic environments.